2017
DOI: 10.1128/aac.01008-17
|View full text |Cite
|
Sign up to set email alerts
|

Ceftazidime-Avibactam and Aztreonam, an Interesting Strategy To Overcome β-Lactam Resistance Conferred by Metallo-β-Lactamases in Enterobacteriaceae and Pseudomonas aeruginosa

Abstract: Ceftazidime-avibactam and aztreonam, an interesting strategy to overcome β-lactam resistance conferred by metallo-β-lactamases in Enterobacteriaceae and Pseudomonas aeruginosa. Antimicrob Agents Chemother 61:e01008-17.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(88 citation statements)
references
References 3 publications
1
82
0
5
Order By: Relevance
“…The other three patients died as a result of other underlying conditions and therefore should not be considered a failure of the combination treatment (249). Several case reports have also demonstrated that the combination of aztreonam and ceftazidime-avibactam can successfully treat infections with NDM-positive CRE strains (247,250). This combination could be considered if there are no alternative therapeutic options, and its efficacy warrants further, large-scale studies.…”
Section: Aztreonam-avibactam or Aztreonam Combined With Ceftazidime-amentioning
confidence: 99%
“…The other three patients died as a result of other underlying conditions and therefore should not be considered a failure of the combination treatment (249). Several case reports have also demonstrated that the combination of aztreonam and ceftazidime-avibactam can successfully treat infections with NDM-positive CRE strains (247,250). This combination could be considered if there are no alternative therapeutic options, and its efficacy warrants further, large-scale studies.…”
Section: Aztreonam-avibactam or Aztreonam Combined With Ceftazidime-amentioning
confidence: 99%
“…have attracted some attention to the potential effect of combining ceftazidime-avibactam with aztreonam. Synergistic effects have been seen in in vitro and in vivo studies (346,357), and indeed, some patients were successfully treated with this combination (208,397). This raises the possibility of using atypical combinations of BLBLIs and other ␤-lactams, such as piperacillin-tazobactam plus aztreonam, against MBL and ESBL producers, although many of these should be tested in vitro, in vivo, and on patients before any recommendations can be provided.…”
Section: Ceftazidime-avibactammentioning
confidence: 99%
“…A relatively new option for treatment of NDM-1 infections is the combination of ceftazidime/avibactam with aztreonam. 6, 7 Aztreonam is active against most MBLs, but often the bacteria have other resistance mechanisms (e.g. ESBLs) that inactivate aztreonam.…”
Section: Discussionmentioning
confidence: 99%
“…5,12 This could be expected to be even worse in a black market, unli- aztreonam. 6,7 Aztreonam is active against most MBLs, but often the bacteria have other resistance mechanisms (e.g., ESBLs) that inactivate aztreonam. The use of the β-lactamase inhibitor avibactam enables aztreonam to remain stable against inactivation despite in vitro resistance to both aztreonam and avibactam individually.…”
Section: Discussionmentioning
confidence: 99%